(untitled) (Studia Prawnicze / The Legal Studies, 1985)
The International Law Commission has been charged with the preparation of two draft conventions — the Draft Code of Offences against the Peace and Security of Mankind, and a draft convention on State responsibility, both of which touch on the question of criminal responsibility. The 1954 Draft Code, and it seerfis the present Draft as well, do not however envisage any penal responsibility of States, confining themselves to the punishment of the "responsible individuals". On the other hand, the sole subjects of the draft on State Responsibility are States. The present article attempts to determine hte legal source of the criminal responsibility of individuals and States. One would assume that the State being the primary (original) person of international law is as well a subject of international penal rules. The position of the individual in international law — on the other hand, — is at least controversial. However; international practice in the field of international penal law tends to the contrary. The subjectivity of an individual in international law can only be explained if treaty rules are addressed directly to the individual and a legal relationship has been established. The relationship between the individual and the treaty is a potential one, and can be compared with the relationship created by a treaty stipulating a right or obligation for a third State. The legal relationship is established in result of a legal fact or event, i.e. when the beneficiary makes use of the right or the obligated individual violates the imposed rule. Thus, the individual becomes a subject of international rules. The status of the State in international law needs no explanation. It is controversial, however, whether a State as a collective unit can bear penal responsibility The practice proves that the State, State organs commit internationally injurious acts not acting privately but in exercise of their official functions. However, in the light of lex lata only criminal responsibility of individuals which were acting on behalf of the State has been so far considered. An exception are th e measures which were applied towards Germany after World War II, and which were beyond the customary notion of compensation. The works of the ILC on the codification of the two conventions will show to what extent the concept of a special or even penal responsibility has been accepted by opinio juris